Kausalitas Fasilitas, Bukti Fisik, dan Kualitas Pelayanan terhadap Keputusan Mengunjungi Transmart Majapahit Semarang - Firdaus; Jumai; Sulistiyaningsih, Sri; Astono, Ari Dwi; Jatmiko, M.Roby; Martini (Business Perspective Journal, 2024)
The retail world is a business that is quite developed in Indonesia, especially since licensing and ownership has been made easier by the government, both direct establishment and franchising. This research aims to describe the causality between the variables of facilities, physical evidence, and services on the decision to visit the Transmart in Majapahit, Semarang. The population in this study were visitors to the Transmart mall in Majapahit, Semarang. The research sample consisted of 100 respondents who met the sampling criteria (purposive sampling). Data collection was carried out in a structured manner through an instrument (questionnaire) with a Likert scale of 1-10, the data collected was processed with the help of SPSS. The results of this research show that complete facilities can be one of the factors for consumers visiting Transmart. Apart from that, this research also shows that physical evidence in the form of magnificent buildings and excellent service from mall staff or employees can be a strengthening factor for consumers. visit. In this research, service is the thing that is most looked at by consumers, this also indicates that Transmart Majapahit needs to improve its services from all existing aspects. Keywords: facilities, physical evidence, services quality, visit decisions, transmart